Estimation of Settling Velocity and Floc Distribution through Simple Particles Sedimentation Experiments - Uk-Jae Lee; Ki-Seong Hyeong; Hong-Yeon Cho (Journal of Marine Science and Engineering, 2020)
The tailings that remain after the collection and screening of Mn nodules are directly discharged into the ocean and are anticipated to influence the ocean environment and marine organisms. The primary factors determining the influence (diffusion) range are the ocean currents and the settling velocity of the tailings; the latter is directly correlated with the time that the tailings remain in the water column. Flocculation is affected by the actual tailing discharge conditions. The settling velocity of the tailings is expected to increase as a result of flocculation; therefore, data on the size distribution of flocs are needed to compute the settling velocity of the tailings. In this study, a method for estimating the floc size distribution of the tailings is proposed, and the general flocculation process is analyzed using the apparent settling velocity, which is readily estimated by simple settling experiments conducted with standard tailings at different concentrations. The apparent falling time-curve followed a power function, and the flocculated grain size was 3–4 times larger than that before flocculation. In addition, flocculation and falling were significantly inhibited by the time required for flocculation. The method suggested in this study was validated by using a numerical particle-tracking model based on the autoencoder concept, which estimates the apparent settling velocity using the flocculated grain size distribution. The computed time-velocity curve agreed well with the apparent time curve obtained in the experiment, with an error of approximately 5–10% except in the initial time range (0–30 s), despite the qualitative nature of the assumptions.